PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA ADABIAH 2 PADANG - Hardewita, Shintia (Jurnal Edukasi dan Penelitian Matematika, 2023)
The mathematics curriculum emphasizes problem solving. This skill can help learners understand mathematical concepts and solve complex problems by making them more concrete. Experience in the field shows that this ability is still weak. Daily tests on SPLTV material in Class X of SMA Adabiah 2 Padang TP 2022/2023 show this inability. Problem-based learning (PBL) can overcome this problem. This study aims to determine whether students taught with PBL can solve math problems better than those taught directly and how this ability develops. This research is quasi-experimental and descriptive and uses a static group design. The population was grade XI of Adabiah 2 Padang High School. Quizzes and tests showed that the PBL approach improved all indicators. Hypothesis results showed rejection of H0 because P-value < α. Then, learners with PBL solve math problems better than direct learning.Keywords– Problem Based Learning, mathematical problem solving abilities